Systemically Administered Ligands of Toll-Like Receptor 2, -4, and -9 Induce Distinct Inflammatory Responses in the Murine Lung - H. Ehrentraut; R. Meyer; M. Schwederski; S. Ehrentraut; M. Velten; C. Grohé; P. Knuefermann; G. Baumgarten; O. Boehm (Hindawi Limited, 2011)
Objective. To determine whether systemically administered TLR ligands differentially modulate pulmonary inflammation. Methods. Equipotent doses of LPS (20 mg/kg), CpG-ODN (1668-thioat 1 nmol/g), or LTA (15 mg/kg) were determined via TNF activity assay. C57BL/6 mice were challenged intraperitoneally. Pulmonary NFκB activation (2 h) and gene expression/activity of key inflammatory mediators (4 h) were monitored. Results. All TLR ligands induced NFκB. LPS increased the expression of TLR2, 6, and the cytokines IL-1αβ, TNF-α, IL-6, and IL-12p35/p40, CpG-ODN raised TLR6, TNF-α, and IL12p40. LTA had no effect. Additionally, LPS increased the chemokines MIP-1α/β, MIP-2, TCA-3, eotaxin, and IP-10, while CpG-ODN and LTA did not. Myeloperoxidase activity was highest after LPS stimulation. MMP1, 3, 8, and 9 were upregulated by LPS, MMP2, 8 by CpG-ODN and MMP2 and 9 by LTA. TIMPs were induced only by LPS. MMP-2/-9 induction correlated with their zymographic activities. Conclusion. Pulmonary susceptibility to systemic inflammation was highest after LPS, intermediate after CpG-ODN, and lowest after LTA challenge.